Sustainable finance for landscape restoration in Spain - Yue, Tao; Geoffroy, Paula Arellano; Schoenmaker, Dirk; Mulder, Arjen; Moolenaar, Simon (London : Rotterdam School of Management, Erasmus University, 2019)
Commonland has the ambition to restore 100 million hectares of degraded land worldwide by 2040 - 5% of the 2 billion hectares of degraded land on the planet. Altiplano Estepario in Southern Spain, that encompasses 1 million hectares, is one of its successful restoration initiatives. However, in order to scale up the existing projects in Spain, and in other parts of the world, Commonland first needs to convince local farmers that it is financially attractive for them to switch from conventional farming to sustainable farming combined with reforestation. Only after having the farmers' financials analysed, can Commonland approach public and private investors with a concrete proposal for long-term funding. What should the financials for the farmers look like? What proposal can Commonland make to investors?
Originally Published InYue, T., Geoffroy, P. A., Schoenmaker, D., Mulder, A. & Moolenaar, S. (2019). Sustainable Finance for Landscape Restoration in Spain. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Landscape protection -- Citizen participation; Landscape protection -- Finance -- Spain